Comparative Study between ADMS and CFD in Modeling Dust Dispersion from a Blasting Events in Quarry - Rinaldi, Wahyu; Mukhriza, Teuku (Jurnal Rekayasa Kimia & Lingkungan, 2011)
Two frequently used methods in atmospheric dispersion modeling (ADMS and CFD) were compared in this study to predict pit retention within an open quarry. Conventional Gaussian plume models developed by CERC, ADMS 3 and ADMS 4, were used to predict the pit retention. This study mimicked Fluent CFD modeling of dust dispersion of a blasting event in Old Moor Quarry. A single blast event that liberated a typical 25,000 tons of rock released 1,900 kg of Total Suspended Particle (TSP). The emission source geometry was defined as a three dimensional block volume source of 70 m normal to the face, 80 m in width and 20 m in height. It was also assumed the TSP liberated over one hour had an emission rate of 4.71x10-3 g/m3/s. The four particle sizes were defined as 2.5, 10, 30 and 75 m at mass fractions of 0.05, 0.45, 0.3 and 0.2 respectively and the particles were assumed have uniform limestone density of 2600 kg/m3. The results indicated that ADMS and model based on CFD indicates similar trend, that is, pit retention is proportional to distance from source to pit edge along wind direction and proportional to inverse quarry gradient.Keywords: dust dispersion, blasting, ADMS, CFD, pit retention